PENGEMBANGAN KOMIK SEBAGAI MEDIA PEMBELAJARAN PADA MATERI IKATAN KIMIA (Siswa Kelas X Sman 1 Benai) - Rabiul Yuselita; Nofri Yuhelman; Rosa Murwindra (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2019)
This research is research and development (R&D) aims to determine the feasibility of the media Comics developed as learning media on chemical bonds class X high school. This research was carried out at Benai 1 High School and was limited tested to 10 students in MIPA 5. Class X The feasibility of this comic media was seen from the validity of the material experts, media experts and students' responses to comic media. The results obtained showed that the developed comic media was suitable for use, evidenced by validation data from material experts and media experts respectively 92%, 84.4% included in the very feasible category and student responses to comic media gained a percentage of 96.3% included in the category of very positive responses. Kata Kunci: Media Pembelajaran, Komik, Ikatan Kimia